Multiple ontologies of Alzheimer's disease in Still Alice and A Song for Martin: A feminist visual studies of technoscience perspective. Issue 4 (November 2019) - Lukić, Dragana
The prevalence of dementia is increasing worldwide but there is still no hope of a cure. Huge resources go into biomedical research, whose reductive 'enactment' has severe consequences for women, who are predominantly affected by dementia. To challenge such tragic enactment, this article considers 'multiple ontologies' of the most common type of dementia – Alzheimer's disease (AD) – in the popular fictional film adaptations Still Alice (2014) and A Song for Martin ( En sång för Martin, 2000). Using a post-humanist account of feminist visual studies of technoscience, this comparative film analysis reveals how gender supersedes AD oversteering the hierarchical dualisms between health and pathology, human and nonhuman, and biomedical and artistic modes of knowing about Alzheimer's. The author argues that these films stress the potential of the arts (dramatic arts and music), as a multisensorial post-humanist embodied state of becoming with AD, to challenge hierarchical dualisms and innovatively contribute to dementia care.